The Rights of Women in Islam: Reconstruction of Haifa A. Jawad’s Thought - Ghoniyah, Sofi (Proceeding International Conference on Religion, Science and Education, 2024)
Women have equal status with men. Before the advent of Islam, either in Arab countries or other countries, women were treated as servile and worthless creatures. A woman could not live freely or treat and organize her life by herself. Then Islam came to provide the rights and freedom of women and honor them without oppressing them. Women deserve education, work, and marriage to whoever they want, offering divorce when it is impossible to continue marital life, stipulating monogamy in marriage, returning circumcision to women because it is an unjust process for women, and they deserve a share in the inheritance as Islam divided it without injustice, and participation in the political issue. This research aims to present the rights of women granted by Islam based on points summarized by Haifa A. Jawad in her book “The Rights of Women in Islam”.